UV exposure of polymeric geomembranes - Lodi, P. C. [UNESP]; Bueno, B. S.; Vilar, O. M. (Zhejiang Univ Press, 2008)
The break of polymer chemical bonds may occur due to penetration of sun short wavelengths. In sanitary landfills for instance, ultraviolet radiation affects uncovered materials and can be dangerous during the installation of the liner and before the placement of the waste. Only the ultraviolet part of the light is harmful to the geosynthetic materials, moreover, each material is sensitive to a particular wavelength. This article evaluates the effects of UV degradation and condensation in black HDPE (1.0 and 1.5 mm) and white HDPE (textured - 1.0 mm) geomembrane that were tested in laboratory during 6 months. The tests were performed using a weatherometer assembled at EESC-USP in accordance to ASTM G154. The results have shown variations in punction and tear resistance after each period of exposure.
Keywords: geomembranes; UV exposure; punction resistance; tear resistance